What Is a Kamisar? - LaFave, Wayne R. (2004)
My good and old friend Yale Kamisar is said to be retiring after a remarkable life in academe spanning almost half a century. I deem it my extraordinary good fortune to have been able to count Yale as a friend for thirty-seven of those years (not that we were enemies the rest of the time), and to have been able to serve as a collaborator of his, working together in the vineyards of the law, for virtually the entirety of our acquaintance. And thus I am especially delighted to have this opportunity to offer up a fair and balanced appraisal and assessment of Yale as he settles into his new-found status of alter kocker